Cats - MacMillan, Kathy, 1975- (Early animal encyclopedias., 2023)
"This early encyclopedia introduces readers to many cat breeds. From hairless cats to cats with curly fur or ears, each breed is special in its own way. This book highlights each cat's appearance, behavior, and history. It also features a map of the breed's place of origin. Features include a glossary, additional resources, and an index. Aligned to Common Core Standards and correlated to state standards. Early Encyclopedias is an imprint of Abdo Reference, a division of ABDO."--Amazon.